The impact of vocational training on labor market outcomes in the Philippines. - Vandenberg, Paul; Laranjo,Jade (ADB economics working paper series, 2020)
The paper analyzes how post-secondary technical and vocational education and training (TVET) impacts labor market outcomes in the Philippines.